Prostaglandin therapy for post partum clinical endometritis - Jacob T C (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1993)
The object of the investigation was to evaluate the therapeutic values of PGF2 alpha, for evolving a non antibiotic alternative for the treatment of post partum clinical endometritis. For this, 42 cross-bred cows, belonging to University Livestock Farm, Mannuthy, having post partum clinical endometritis were divided into four groups. Group I consisted of 10 animals which were watched for their natural oestrus and inseminated twice at 24 hours interval. In group II, II animals were observed for their natural oestrus and inseminated twice at 24 hours interval and were given post insemination intrauterine antibiotic treatment 24 hours later based on antibiotic sensitivity test. Eleven animals in group III were subjected to induction of oestrus by administration of PGF2 ALPHA (Lutalyse) 25 mg intramuscular 8-12 days of their cycle and inseminated twice at 24 hours, at the induced oestrus. Group IV consisted of 10 animals subjected to induction of oestrus as in group III and inseminated twice at 24 hours interval and were given post insemination intrauterine antibiotic therapy based on sensitivity tests, 24 hours later. The observations made and inferences drawn are given below. The interval from the administration of PGF2 alpha to the onset of oestrus ranged from 48-120 hours (mean 61.81 hours) and 36 to 72 hours (mean 54.0 hours) in group III and IV, respectively. The mean duration of oestrus was 21.6 hours, 23.36 hours, 28.36 hours and 31.60 hours in the four groups respectively. The duration of oestrus showed significant variation between groups I and IV (t’ = 28910) and between groups II and IV (t’ = 2.6445). The percentage of intense, medium and weak oestrus was 66.66, 23.80 and 9.52 per cent respectively in natural oestrus and 66.66, 19.04 and 14.28 in induced oestrus respectively. The difference in the intensity of oestrus between natural and induced oestrus was not significantly different, although, a slightly high incidence of weak oestrus was observed, when oestrus was induced with Lutalyse. Physical changes of the reproductive tract like oedema of the vulva, congestion of vulval mucosa and sliminess did not show any variation between the natural oestrus and induced oestrus. The percentage of animals showing purulent discharge, discharge with flakes and cloudy discharge showed a marked reduction when treated with PGF2 alpha alone and a combination of PGF2 alpha and antibiotics. Similarly the percentage of animals showing clear discharge increased enormously by above treatments. The bacterial organisms isolated from the uterine discharges were citrobacter spp. 23.84 per cent, Bacillus spp. 23.80 per cent, S. aureus 14.28 per cent, Pseudomonas 14.28 per cent, Corynebacterium spp. 9.52 per cent, coagulase negative staphylococci, 9.52 per cent and the yeast Canida guilliermondii 4.76 per cent. Gentamicin was the most sensitive antibiotic for most of the organisms isolated, followed by chloramphenicol, oxytetracycline and sulphadiazine. Penicillin was the most resistant followed by streptomycin and nitrofurantoin. Significant difference in the overall conception rate was observed between different groups; the overall conception rate was significantly higher in group IV than in group I and II (t’ = 4.8341 between groups I & IV and t’ = 2.9186 between groups II & IV). Significantly higher conception rate was observed in group III than group I also (t’ = 5.5886). The number of inseminations required per conception was lowest in group III and highest in group I. Thus, it appeared that PGF2 alpha in combination with antibiotic was beneficial in the treatment of clinical endometritis. But since the number of inseminations required for conception was lower in group III than group IV and because, there is no significant difference in the overall conception rate, between these two groups, it could be inferred that administration of antibiotics along with PGF2 alpha did not have any added advantage. Furthermore, considering the harmful effects of administration of antibiotics, it may be stated that PGF2 alpha alone would be beneficial in the treatment of post partum clinical endometritis and can be recommended as the drug of choice.